2021
DOI: 10.3390/biology10060467
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Histone Deacetylase 6 Decreases Cellular Malignancy and Contributes to Primary Cilium Restoration, Epithelial-to-Mesenchymal Transition Reversion, and Autophagy Inhibition in Glioblastoma Cell Lines

Abstract: Glioblastoma multiforme, the most common type of malignant brain tumor as well as the most aggressive one, lacks an effective therapy. Glioblastoma presents overexpression of mesenchymal markers Snail, Slug, and N-Cadherin and of the autophagic marker p62. Glioblastoma cell lines also present increased autophagy, overexpression of mesenchymal markers, Shh pathway activation, and lack of primary cilia. In this study, we aimed to evaluate the role of HDAC6 in the pathogenesis of glioblastoma, as HDAC6 is the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…In line with these studies, aberrant expression of tubulin deacetylase HDAC6 has been reported in several cancer cell lines and tumor models [70,71]. In addition, upregulation of HDAC6 increases cell motility in breast cancer cells, thus contributing to cancer metastasis [72], whereas in glioblastoma cells genetic silencing of HDAC6 decreases cellular malignancy and reverses the mesenchymal phenotype [73,74]. High level Lung Treatment response to paclitaxel [64] On the other hand, the role of tubulin deacetylase SIRT2 in cancer is controversial, as SIRT2 exerts either tumor-suppressive or oncogenic properties.…”
Section: The Tubulin Code and Its Associated Enzymes In Cancermentioning
confidence: 72%
See 1 more Smart Citation
“…In line with these studies, aberrant expression of tubulin deacetylase HDAC6 has been reported in several cancer cell lines and tumor models [70,71]. In addition, upregulation of HDAC6 increases cell motility in breast cancer cells, thus contributing to cancer metastasis [72], whereas in glioblastoma cells genetic silencing of HDAC6 decreases cellular malignancy and reverses the mesenchymal phenotype [73,74]. High level Lung Treatment response to paclitaxel [64] On the other hand, the role of tubulin deacetylase SIRT2 in cancer is controversial, as SIRT2 exerts either tumor-suppressive or oncogenic properties.…”
Section: The Tubulin Code and Its Associated Enzymes In Cancermentioning
confidence: 72%
“…In line with these studies, aberrant expression of tubulin deacetylase HDAC6 has been reported in several cancer cell lines and tumor models [ 70 , 71 ]. In addition, upregulation of HDAC6 increases cell motility in breast cancer cells, thus contributing to cancer metastasis [ 72 ], whereas in glioblastoma cells genetic silencing of HDAC6 decreases cellular malignancy and reverses the mesenchymal phenotype [ 73 , 74 ].…”
Section: The Tubulin Code and Its Associated Enzymes In Cancermentioning
confidence: 99%
“…Glioblastoma is associated with high levels of the mesenchymal markers Snail, Slug, and N-cadherin. Glioblastoma cell lines show high levels of autophagic flux and activation of the sonic hedgehog (Shh) pathway [ 9 ]. HDAC6 is the most overexpressed isoform in glioblastoma [ 9 ].…”
Section: Role Of Hdac6 In Cancer Cell Proliferationmentioning
confidence: 99%
“…The three mixed phosphorylated polypeptides derived from GLI2 significantly increased the level of GLI2 phosphorylation and decreased the transcriptional activation of GLI2, and the radiation sensitization of GBM cells was significantly higher than that in the control group ( 128 ). HDAC6 was upregulated in GSCs and inhibited HDAC6 down-regulated glioma-associated oncogene GLI1 and PTCH1/2 receptors, as well as SHH signaling components, expression and activity, thereby inhibiting GSC proliferation, inducing differentiation and increasing the apoptosis rate through the SHH/GLI1 signaling pathway ( 109 , 129 ). Inhibition of HDAC6 by Tubasatin A enhanced the radiosensitivity of GBM tumor cells.…”
Section: Targeting the Hh Signaling Pathway In Gbmmentioning
confidence: 99%